Reconciling Hadiths on Tolerance and Warfare: A Mukhtalif al-Ḥadīth Study on Muslim-Non-Muslim Relations - Amrullah; Amin, Muhammaddiyah; Ahmad, La Ode Ismail; M. Ilham (International Journal of Islamic Thought and Humanities, 2025)
Hadith is a source of Islamic teachings that has a great influence in shaping the social ethics of Muslims, including in establishing relations with followers of other religions. However, a number of textually contradictory hadiths have been found between the call for tolerance and the order of war against non-Muslims. This study aims to analyze and reconcile the meaning of these traditions through a qualitative approach based on a literature study, using a descriptive-analytical method. The approach of mukhtalif al-ḥadīs and supported by the framework of maqāṣid al-syarī'ah to interpret the purpose of Islamic law as a whole. The results show that the traditions on tolerance apply in peaceful situations and contain the principle of protection of human life, religion, and honor. In contrast, the war traditions are understood contextually as responses to real threats or violations of peace treaties, not as instruments of theological aggression. Thus, the study asserts that reconciliation of the hadith is only possible through a historical, contextual and teleological approach that does not separate the text from the overall purpose of the Shari'ah. The implication of this study is the importance of understanding the hadith as a whole so that it is not used to justify violence in the name of religion.